Synthesis, Characterization, Biological Activity and Molecular Docking Studies of Novel Organotin(IV) Carboxylates - Muhammad, Niaz; Ahmad, Mukhtar; Sirajuddin, Muhammad; Ali, Zafar; Tumanov, Nikolay; Wouters, Johan; Chafik, Abdelbasset; Solak, Kübra; Mavi, Ahmet; Muhammad, Shabbir; Shujah, Shaukat; Ali, Saqib; et al. (Frontiers in Pharmacology, 2022)
Four new carboxylates complexes with general formula R2SnL2 and R3SnL, where R = n-butyl (1, 3), methyl (2, 4) and L = 4-Chlorophenoxyacetate, were synthesized in significant yields. FT-IR analysis revealed a chelating (1 and 2) and a bridging bidentate (3 and 4) coordination modes for the carboxylate ligand in solid state which was further confirmed by the single crystal X-ray analysis of complex 4. The NMR data (1H, 13C and 119Sn) revealed a higher coordination number around the tin center in R2SnL2 (1 and 2) compared to R3SnL (3 and 4). A close matching was observed between the experimental and calculated structures (obtained at B3LYP/6-31G*+LANL2DZ basis set). Quantum chemical analysis indicates that the carboxylate moiety has the major contribution in the formation of filled and unfilled orbitals as well as in ligand to ligand intramolecular charge transfer during the electronic transitions. The cytotoxicity data of the screened compounds evaluated against lung cancer cell line (A549) and normal lung fibroblast cell line (MRC-5) revealed that 1, 3 and 4 have shown dose dependent cytotoxic effects while HL and 2 have shown steady and low cytotoxic activities. The antibacterial activity of complexes 1-4 is higher than that of HL. Molecular docking study showed an intercalation binding mode for complex 3 with DNA (docking score = -3.6005) involving four polar interactions. Complex 3 docking with tubulin (PDB ID 1SA0) with colchicine as a target protein resulted in three polar interactions (docking score -5.2957). Further, the docking analysis of the HL and 1-4 has shown an adequate interactions with the coronavirus SARS-CoV-2 spike protein, nucleocapsid protein and human angiotensin converting enzyme (ACE2).